How does Rasch modeling reveal difficulty and suitability level the fraction test question? - Karlimah Karlimah (Jurnal Elemen, 2022)
This article explains how to analyze test items in arithmetic operation with fractions to obtain the items' level of difficulty and fitness. Data were collected by using multiple-choice questions given to 50 fourth-grade students of an elementary school in Tasikmalaya city. The answers were then analyzed using the Rasch model and Winsteps 3.75 application, a combination of standard deviation (SD) and logit mean values (Mean). The score data of each person and question were used to estimate the pure score in the logit scale, indicating the level of difficulty of the test items. The categories were difficult (logit value +1 SD); very difficult (0.0 logit +1 SD); easy (0.0 logit -1 SD); very easy (logit value –SD). Three criteria were used to determine the level of difficulty and fitness of the questions: the Outfit Z-Standard/ZSTD value; Outfit Mean Square/MNSQ; and Point Measure Correlation. It resulted in a collection of test items suitable for use with several levels of difficulties, namely, difficult, very difficult, easy, and very easy, from the previous items, which had difficult, medium, and easy categories. Rasch model can help categorize questions and students' ability levels.